Evidence on Tax‐Motivated Securities Trading Behavior - BADRINATH, S. G.; LEWELLEN, WILBUR G. (Journal of Finance, 1991)
ABSTRACT Tax‐loss selling by investors in common stocks near the end of calendar years has been proposed as an explanation for the turn‐of‐the‐year effect in stock returns. Past analyses of this hypothesis have relied on inferential data. We provide here some direct data from a compilation of over 80,000 actual common stock investment round trips by a sample of 3000 individual investors. We find strong evidence of a concentration of loss‐taking trades late in the year and milder evidence of a concentration just prior to the dates when investments become eligible for long‐term tax treatment.